School mediation in the training of literary readers in secondary school students - Santillán Leaño, Ángel Elipio (2022)
The purpose of this research was to identify the effectiveness of school mediation in the training of literary readers, as a proposal to improve the cultural practice of literary reading in secondary school students. This proposal is relevant because it responds to the reading crisis, which is a wide-ranging sociocultural problem that manifests itself, in secondary school students, in low reading performance and which, of course, affects the development of competence. reader and civic education. The study was developed under the methodology of a quantitative research, with an experimental design (quasi-experimental) with a population of 546 students and a non-probabilistic sample of 103, corresponding to educational institutions: Isaac Newton and Von Neumann:experimental group and control group, with 54 and 49 students, respectively. The application of the proposal was executed through twelve workshop sessions through school mediation, whose information from the pre and post-test was collected using instruments: survey questionnaire, literary comprehension practice and the rubric; and they were analyzed through descriptive and inferential statistics, the results of which show a 13% progress in literary training. The hypothesis test indicates, for its part, that school mediation positively influences the training of literary readers of secondary school students with a significance level of ρt (0.05), t= -9.76